2008
DOI: 10.1021/jf072970c
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Contribute to Dark Bran Pigmentation in Hard White Wheat

Abstract: Unacceptably dark bran color has prevented the white-kernelled variety Argent from meeting grain color marketing standards for hard white wheats (Triticum aestivum L.). The objective of this research was to identify phenolic compounds that negatively affect bran color in white wheat using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) and vanillin-HCl and NaOH staining methods. In mature bran, FT-ICR-MS detected derivatives of the flavonol quercetin in varieties Argent and RL4137 (red-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…In addition, numerous studies investigated the pharmacological activity of stilbenes, in particular the antioxidant, anti-inflammatory and anticarcinogenic effects of resveratrol and pinosylvin [47][48][49][50][51]. Although very few studies reported on stilbene occurrence in wheat, two pinosylvin derivatives were described by Matus-Cádiz et al [17]. Proanthocyanidins are a class of colorless phenolics characterized by an oligomeric or polymeric structure, based on flavanol units.…”
Section: Other Chemical Classes (Coumarins Stilbenes Proanthocyanidmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, numerous studies investigated the pharmacological activity of stilbenes, in particular the antioxidant, anti-inflammatory and anticarcinogenic effects of resveratrol and pinosylvin [47][48][49][50][51]. Although very few studies reported on stilbene occurrence in wheat, two pinosylvin derivatives were described by Matus-Cádiz et al [17]. Proanthocyanidins are a class of colorless phenolics characterized by an oligomeric or polymeric structure, based on flavanol units.…”
Section: Other Chemical Classes (Coumarins Stilbenes Proanthocyanidmentioning
confidence: 99%
“…The interpretation of mass spectra allowed the identification of 34 phenolic compounds (104 including isomer forms) in the 22 investigated genotypes. Most of the detected polyphenols were previously described in wheat in other reports [13,14,16,17,31,32]. As outlined below, compounds were grouped into chemical classes and structural formulae of representative compounds are shown in Fig.…”
Section: Hplc-esi-tof-ms Optimization and Identification Of Phenolic mentioning
confidence: 99%
See 2 more Smart Citations
“…Grain colour is of a primary concern as the presence of darker kernels may be considered a disadvantage particularly in markets where Australian white wheat is considered the standard (Bason, Zounis, Ronalds, & Wrigley, 1995;Reifschneider, 2003). Several researchers (Bequette & Herrman, 1994;Bason et al, 1995;Wu, Carver, & Goad, 1999;Peterson et al, 2001;Matus-Cádiz, Hucl, Perron, & Tyler, 2003;Matus-Cádiz et al, 2008;Lukow, Adams, Suchy, DePauw, & Humphreys, "in press") have reported that there is variability in the white-seeded varieties with seed coats ranging from very white and pasty to reddish in colour.…”
Section: Introductionmentioning
confidence: 99%